Pseudotanais Sars, 1882 (Crustacea: Tanaidacea) From the SE Australian Slope: A Gap in Our Knowledge - Błażewicz, Magdalena; Jakiel, Aleksandra; Bird, Graham J. (Frontiers in Marine Science, 2021)
In the current paper, we present the description of five new species of pseudotanaids sampled off the Bass Strait during two campaigns (SLOPE), which took place in 1986/8 and 1994 from the upper continental margin (slope) at depths 200–1550 m, hopefully starting to fill a gap in the knowledge of this major habitat. From five species, two occurred off eastern coast between Gippsland and Jervis Point and three others on the southern coast between Great Otway (Otway Point) and Kangaroo Island. These five species bring the total number of described pseudotanaid species 94 and to six in Australian waters.